Grupo operativo como ferramenta de supervisão para profissionais que atuam com grupos de inspiração psicanalítica - Andrade, Rodrigo Mostaço (2023)
One essential technique for organizing and leading groups with a psychoanalytic bent is supervision. Operative groups have historically been employed in private projects, public health institutions, and social aid programs. With professionals who coordinate groups and their theoretical systematization, and taking into account the advantages in health promotion, training, teaching, and learning, as well as group supervision, work tools are produced for those who must supervise groups as well as for those who are faced with practicing in groups. Objective: Monitor and oversee the activity of operative groups through operactive groups, confirming how learning about the subject will be incorporated and assimilate, detecting emerging content in the group environment, and mediating the promotion of teaching and learning. Methods: Qualitative research with experts in the administration and arranging of groups with a psychoanalytic influence. This study involved seven psychologists involved in the "Novo Olhar" initiative. Clinical case supervision, which lasted one hour and involved ten meetings overall, was conducted every two weeks for the purpose of gathering data. Each meeting concluded with the creation of a field journal with data for examination. Results and Discussion: By incorporating and assimilating the offered knowledge, the operational oversight group was able to support teaching and learning. Additionally, because the group environment allows for the exchange of ideas and affections, it has the potential to support the participants' mental health in other ways.